Problem-Based Learning Model to Improve High School Students' Knowledge of Athletics Sports Material Learning Achievement - Pratomo, Eko Setya (ETDC: Indonesian Journal of Research and Educational Review, 2024)
The objective of this study was to determine the improvement of student learning achievement in athletics material through the problem-based learning model. This type of research is classroom action research with two cycles. At MA Al-Hikmah Purwoasri, the research sample consisted of 24 students. We conducted this research through a cycle of planning, implementation, observation, reflection, and data collection. The instruments used in this study were test and observation techniques. The data analysis used a quantitative description. The results of the study showed that there was a significant increase in student athletics learning achievement after the problem-based learning model was implemented. This is clear from the results of cycle I, where 47% of the students did not meet the minimum completion criteria of 75, and the class average was only 78.01. On the other hand, cycle II results showed that 91.18% of the 24 students who took the test met the minimum completion criteria of 75. Therefore, the application of the problem-based learning model can enhance student learning achievement in athletics material, particularly in the high jump.